Spatial organisation of fungi in soil biocrusts of the Kalahari is related to bacterial community structure and may indicate ecological functions of fungi in drylands - Elliott, David R.; Thomas, Andrew D.; Hoon, Stephen R.; Sen, Robin (Frontiers in Microbiology, 2024)
Biological soil crusts, or biocrusts, are microbial communities found in soil surfaces in drylands and in other locations where vascular plant cover is incomplete. They are functionally significant for numerous ecosystem services, most notably in the C fixation and storage due to the ubiquity of photosynthetic microbes. Whereas carbon fixation and storage have been well studied in biocrusts, the composition, function and characteristics of other organisms in the biocrust such as heterotrophic bacteria and especially fungi are considerably less studied and this limits our ability to gain a holistic understanding of biocrust ecology and function. In this research we characterised the fungal community in biocrusts developed on Kalahari Sand soils from a site in southwest Botswana, and combined these data with previously published bacterial community data from the same site. By identifying organisational patterns in the community structure of fungi and bacteria, we found fungi that were either significantly associated with biocrust or the soil beneath biocrusts, leading to the conclusion that they likely perform functions related to the spatial organisation observed. Furthermore, we showed that within biocrusts bacterial and fungal community structures are correlated with each other i.e., a change in the bacterial community is reflected by a corresponding change in the fungal community. Importantly, this correlation but that this correlation does not occur in nearby soils. We propose that different fungi engage in short-range and long-range interactions with dryland soil surface bacteria. We have identified fungi which are candidates for further studies into their potential roles in biocrust ecology at short ranges (e.g., processing of complex compounds for waste management and resource provisioning) and longer ranges (e.g., translocation of resources such as water and the fungal loop model). This research shows that fungi are likely to have a greater contribution to biocrust function and dryland ecology than has generally been recognised.